Fictional videogames as framing devices - Julián Gutiérrez Carrera (Eludamos)
In this paper, I argue that the use of fictional Massively Multiplayer Online games (MMOs) as framing devices serves as a reflexive narrative tool that suggests an understanding of MMOs as spaces with their own internal rules of communication. To do this, I conduct a close reading of Agony of a Dying MMO, a singleplayer demo game that depicts the final hours of service of a fictional MMO through a series of semi-explorable vignettes showing the activities of fictional players. In order to analyse how MMOs are represented as spaces with internal rules of communication, I focus my analysis on three instances of direct suicide communication—communicative acts directly referring to past, present, or future suicidal intent. As suicide communication is often indirect, I focus on how the social logic and rules of MMOs enable direct suicide communication. Through the close readings, I found that MMOs alter, enable, and restrict specific types of communication through a combination of their game design features, their user interfaces, and their existence as (and contiguity with) online spaces. In particular, I found that written communication through an MMO’s chat box can provide an alibi by turning seemingly serious statements into jokes; that acts embedded in the process of engaging with MMOs, like logging out and the consequent disappearance of a character, can serve as a communicative tool denoting finality; and that game design features meant to bring players together, like guilds and factions, can enable player authenticity and openness by attracting like-minded players, for better or for worse. As the use of videogames as framing devices presents a meta-referential commentary on videogames in the real world, these represented social affordances suggest that virtual online spaces provide unique opportunities and alibis for direct suicide communication.